Mealtime and patient factors associated with meal completion in hospitalised older patients: An exploratory observation study. Issue 19 (4th May 2021) - Naughton, Corina; Simon, Rachel; White, T. J.; de Foubert, Marguerite; Cummins, Helen; Dahly, Darren
Abstract: Aims and Objectives: To examine mealtime and patient factors associated with meal completion among hospitalised older patients. We also considered contextual factors such as staffing levels and ward communication. Background: Sub‐optimum nutrition is a modifiable risk factor for hospital associated decline (HAD) in older patients. Yet, the quality of mealtime experiences can be overlooked within ward routinised practice. Design: Cross sectional, descriptive observation study. Methods: We undertook structured observation of mealtimes examining patient positioning, mealtime set‐up and feeding assistance. The outcome was meal completion categorised as 0, 25%, 50%, 75% or 100%. Data were collected on patient characteristics and ward context. We used mixed‐effects ordinal regression models to examine patient and mealtime factors associated with higher meal completion producing odds ratios (OR) and 95% confidence intervals (CI). The study was reported as per STROBE guidelines. Results: We included 60 patients with a median age of 82 years (IQR 76–87) and clinical frailty score of 5 IQR (4–6). Of the 279 meals, 51% were eaten completely, 6% three quarters, 15% half, 18% a quarter and 10% were not eaten at all. Mealtime predictors with a weak association with less‐meal completion were requiring assistance, special diets, lying in bed, and red tray (indicator of nutrition risk), but were not statistically significant. Significant patient‐level factors were higher values for frailty (OR 0.34 [0.11–1.04]) and Malnutrition Universal Screening Tool (OR 0.22 [0.08–0.62]). The average nurse‐to‐patient ratio was 1:5.5. Conclusion: Patient factors were the strongest predictors for meal completion, but mealtime factors had a subtle influence. The nursing teams' capacity to prioritise mealtimes above competing demands is important as part of a comprehensive nutrition strategy. Relevance to clinical practise: Nurses are central to optimising nutrition for frail older patients. It requires ward leadership to instil a culture of prioritising assisted mealtimes, improved communication, greater autonomy to tailor nutrition strategies and safe staffing levels.